The Influence of Project Based Learning LKPD in Improving 21st Century Skills for Class V Elementary School Students - Rina Marlina; Yavelma Miaz; Farida F; Ardipal (Postgraduate, University of Mataram, 2025)
This research aims to provide an influence on the use of Student Worksheets (LKPD) based on Project Based Learning (PBL) on improving 21st century skills in fifth grade elementary school students. The problem raised is the low development of critical thinking, creativity, collaboration and communication skills in students who use conventional learning methods. This research uses quantitative methods with a quasi-experimental design. The research sample consisted of 60 students who were divided into two groups: 30 students in the experimental group who used PBL-based LKPD and 30 students in the control group who used conventional LKPD. The instruments used include skills tests, observation sheets, and student perception questionnaires. Data were analyzed using the t test (t-test). The research results showed that the experimental group experienced a significant increase in critical thinking skills by 18.53%, creativity by 16.82%, collaboration by 19.31%, and communication by 14.21%. Meanwhile, the control group only experienced an increase of 9.11%, 7.62%, 8.43% and 6.71% respectively. In conclusion, PBL-based LKPD is significantly more effective in improving 21st century skills in elementary school students compared to conventional learning methods. These findings support the implementation of PBL as an effective learning strategy at the basic education level.